Accelerating the Clean Energy Transition: Review of Solar Energy Potential, Policy Dynamics, and Economic Challenges for Indonesia’s Net-Zero 2060 Goals - Fhandy Pandey; Melly Angglena (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Indonesia has abundant solar resources yet solar photovoltaic (PV) deployment still lags behind its technical potential. This paper reviews the current status, resource potential and future development of solar energy in Indonesia with a focus on engineering aspects of grid connected and off grid PV systems. Using data and studies from 2015 to 2025, we summarize solar irradiation patterns, installed capacity growth, system performance and levelized cost of electricity for both utility scale plants and rooftop or rural applications. The analysis shows that average solar irradiation of about 4.5 to 5.0 kWh/m² per day and rapidly declining PV costs support large scale deployment, but installed capacity remains around 1 GW in 2025 and contributes only a small share of national generation. Key barriers include coal based lock in, regulatory and investment disincentives, and grid integration constraints. The paper outlines policy, technology and investment pathways needed to unlock Indonesia’s substantial solar potential and support a cleaner grid.